Spectrum of Tuberculosis in the State of Jammu and Kashmir - Abdul Khalid, M.Tariq Baqai,Mateen Khan (Journal of Rawalpindi Medical College, 2012)
Background: To determine the incidence of Tuberculosis in the state of AJK and to formulate suggestion/ strategies in perspective of Millennium Development Goals to control TB. Methods: In this descriptive study, data was collected from sixty Tuberculosis (TB) centres of ten districts of Azad Jammu & Kashmir [AJK]. The patients were registered and provided free treatment with monthly follow ups. The average duration of treatment was eight months with intensive phase of two and maintenance phase of six months. Results:There was a steady increase in the average annual rate of tuberculosis since 1990. It was lowest in 1990 (63/100,000) and highest in 1998 (138/100,000).The average annual rate during the last 10 years was 114.5/100,000 population. The maximum number of new patients (Total 4829) were registered in 2004 whereas the minimum number of patients were registered in 1990(Total 1265). Conclusion: The incidence of TB has not declined in the State.